UDDWE: Universal domain deep web exposer - Singh Sehgal, Manpreet; Shankar Prasad, Jay (International Journal of Engineering and Technology, 2018)
Traditionally, the search engines were able to extract web data which is smaller in size as compared to much relevant and quality data (also called hidden web data) hidden behind search interfaces. A lot of research has been done to extract this web data to fetch its relevant and quality content. However, most of the methods are domain specific i.e. for multiple domains multiple tools are designed. In this paper, a novel method is proposed to present one universal tool for all the domains. The key point in this approach is the customization of the traditional search engine to receive the user query to process it for identifying the entry points (search interfaces) to the hidden web. After this filtering process, the entry points are presented for opening in a controlled programmed environment to ease the data extraction process.